Bacterial AAA+ disaggregase ClpB: mechanism and inhibition - Ranaweera, Chathurange Bharathee (Kansas State University, 2021)
Molecular chaperones are essential proteins that bind to unfolded and partially folded polypeptide chains to prevent their aggregation and precipitation. Many molecular chaperones were first described as heat shock proteins (Hsp) because their expression is increased at elevated temperatures. Bacterial ClpB is a molecular chaperone, which is involved in reactivation of aggregated proteins. ClpB is the only known bacterial chaperone capable of suppressing and reversing protein aggregation in cooperation with other heat-shock proteins (DnaK, DnaJ, GrpE). In the presence of ATP, six ClpB monomers associate and form the hexameric functional unit of ClpB. Our understanding of the mechanism of substrate recognition by ClpB is still limited and is under investigation. In order to study substrate recognition by E. coli ClpB and substrate binding affinity, we used model peptide substrates in fluorescence anisotropy experiments. We hypothesized that the peptides containing predicted aggregation-prone sequences would preferentially bind to ClpB. Our results demonstrated that substrate recognition mechanism of ClpB may build upon global surface properties of aggregated proteins rather than on local sequence motifs. Next, we explored a potential of ClpB as a target for the development of novel antimicrobials. We investigated ClpB activity in the presence of several previously described inhibitor candidates and identified N²,N⁴-dibenzylquinazoline-2,4-diamine (DBeQ) as a promising lead compound for future structural optimization aimed at selective targeting of ClpB and/or DnaK. We also studied protein aggregation patterns in two obligate intracellular pathogenic bacteria, Anaplasma phagocytophilum and Ehrlichia chaffeensis. We performed the first biochemical characterization of ClpB and DnaK from Anaplasma phagocytophilum and investigated substrate recognition mechanisms of ClpB and DnaK from Anaplasma phagocytophilum with similar conclusions to those obtained with E. coli chaperones. Finally, we demonstrated that DBeQ displays a potent activity against both Anaplasma phagocytophilum and Ehrlichia chaffeensis in infected cell cultures. Thus, DBeQ can be used as a lead compound for further development of novel treatments for Human Granulocytic Anaplasmosis (HGA) and Human Granulocytic Ehrlichiosis (HGE).
Keywords: ClpB; DnaK; Protein aggregation; Molecular chaperones; ATPases associated with diverse cellular activities; Heat shock proteins